Dynamics of essentialist representations of nationhood and the politics of interpretation : the role of religion in the making and unmaking of the Sri Lankan nation-state - Fernando, L A Jude Lal (Irish School of Ecumenics, 2008)
Sometimes the impression given of the Lankan conflict by both the local and mainstream media is that the conflict has been caused by primordial or perennial antagonisms that existed between the parties involved. Such a projection adds evidence to the unchecked hypothesis of a ‘clash of civilisations’ that is supposed to be gaining ground in the emerging world order. In my study of the Lankan conflict I argue that it is mainly a modern conflict which has its roots in the colonial and postcolonial state-building.
Keywords: Religions, Peace Studies & Theology, Ph.D.; Ph.D. Trinity College Dublin